Diagnostic Accuracy of Transabdominal Ultrasound in the Diagnosis of Ectopic Pregnancy Taking Transvaginal Ultrasound as the Gold Standard - Sattar, Mamoona; Khan, Shandana (Indus Journal of Bioscience Research, 2024)
Background: The diagnostic accuracy of transabdominal ultrasound in the diagnosis of ectopic pregnancy has rarely been studied in our population. Hence, the study has been planned. Objective: This study aimed to determine the accuracy of transabdominal ultrasound in the diagnosis of ectopic pregnancy, transvaginal ultrasound was used as the gold standard. Materials and Methods: This cross-sectional study was carried out at the Department of Radiology, Northwest General & Research Centre, Peshawar, from 12th June 2022 until 12th December 2022. Patients aged 15–45 years presenting with signs and symptoms of ectopic pregnancy were enrolled. Transabdominal ultrasound was performed, and the diagnostic accuracy was compared with that of transvaginal ultrasound to determine the diagnostic accuracy. The data were analysed via SPSS version 25. Results: A total of 143 patients were enrolled. The mean age of the patients was 30.01±5.518 years. The majority of the patients were aged less than 30 years (n = 84, 58.7%). The sensitivity, specificity, PPV, NPV and accuracy of transabdominal ultrasound were 93.9%, 100.0%, 100.0%, 57.8% and 94.4%, respectively. Conclusion: The clinical spectrum of ectopic pregnancy is very wide. Transabdominal ultrasound is a useful noninvasive diagnostic tool for the diagnosis of ectopic pregnancy.